Composite Narratives with Arts-Based Analysis of Undergraduate Engineering Students’ Stress and Social Supports to Identify Structural Barriers - Jeanne Sanders; Joseph Mirabelli; Eileen Johnson; Karin Jensen (Studies in Engineering Education, 2025)
Background: Undergraduate engineering students experience high stress and exhibit help-seeking behaviors less than non-engineering peers. Developing a deeper, comprehensive understanding of their experiences is a critical step to identifying potential changes to reduce their stress. Research identifying structural components that impact student stress can inform structural changes that decrease student stress and thus support engineering students’ mental health. Purpose/Hypothesis: We examined how narratives of engineering undergraduate experiences with stress highlight the relationship between control and identified hindrances. We then used these relationships to investigate underlying structural elements. Design/Method: We interviewed fourteen undergraduate engineering students at an R2 institution in the northeastern United States. To create narratives, we conducted a tri-fold process that consisted of thematic analysis, identification of key quotes, and arts-based memo analysis. These narratives were mapped onto the Job-Hindrance-Control-Support (JHCS) model to identify structural elements for potential change. Results: The resulting composite narratives of George and Maya presented compelling stories of students’ experiences with stress and social support that highlight underlying structural systems, and their sources of support differed. Identified structural elements impacting their experiences included their physical proximity to campus, financial resources, and support for both time management and social-emotional regulation. Conclusions: Undergraduate engineering students commonly experience high levels of stress, and recognition of identified key structural elements followed by informed, deliberate action may be one way to support student mental health.